The King Jesus Gospel : the original good news revisited - McKnight, Scot. (Grand Rapids, Mich. : Zondervan, 2011)
"The gospel is the declaration that Jesus is Messiah and Lord and that gospel declares that the story of Jesus completes the story of Israel in a way that saves. This gospel counters the shallow and superficial gospeling today that reduces the gospel to four simple points and eliminates the confession that Jesus is Messiah and Lord. Contemporary Christians have built a 'salvation culture' but not a 'gospel culture.' Too many Christians have reduced the gospel to the message of personal salvation. [This book] makes a plea for us to recover the original gospel as 'good news, ' which is still new and still fresh. This book succinctly and without pretense demonstrates that the gospel is defined by the apostles in 1 Corinthians 15 as the completion of the story of Israel in the saving story of Jesus. McKnight shows us that the gospel was preached by Jesus, and that the sermons in the Book of Acts are the best example of gospeling in the New Testament. The King Jesus Gospel ends with practical suggestions about evangelism and about building a gospel culture"--Provided by publisher.
The big question -- Gospel culture or salvation culture? -- From story to salvation -- The apostolic gospel of Paul -- How did salvation take over the gospel? -- The gospel in the gospels? -- Jesus and the gospel -- The gospel of Peter -- Gospeling today -- Creating a gospel culture -- Appendix 1: summary statements in the New Testament -- Appendix 2 : Justin, Martyr, First Apology 66-67 -- Appendix 3 : sermons in Acts.
Includes bibliographical references (pages 178-184).
Keywords: Jesus Christ -- Person and offices -- Biblical teaching; Bible. -- Theology; Evangelistic work